THE IMPACT OF FLASHCARD MEDIA ON STUDENT COGNITIVE IMPROVEMENT IN IPAS SUBJECTS AT ELEMENTARY SCHOOL - Shafa Audrey Maharani; Dita Prihatna Wati (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
In learning activities, problems are still found such as difficulties when explaining the material because there is no concrete learning media so that students' cognitive improvement is not optimal, cognitive abilities in elementary schools still need to be improved. This study aims to develop interactive learning media in the form of Flashcard to improve cognitive grade I elementary school students, with experimental and control types of research on quantitative approaches. The data collection method uses Pretest and Postest questions, with the research population of all 1A class students totaling 25 students and 1C totaling 20 students. The data collected was obtained by independent sample t test because the data was normal. This study concludes the use of Flashcard learning media for cognitive enhancement in class I, this is indicated by the sig value. 0.000 < 0.05 which indicates there is a difference before and after giving action. Therefore, it is stated that the initial hypothesis is rejected and the alternative hypothesis is accepted. So it can be concluded that Flashcard are feasible to use in helping students for the learning process so as to improve the cognitive of grade I elementary school students